Quantifying changes and influences on mottled duck density in Texas. Issue 2 (25th October 2017) - Ross, Beth E.; Haukos, David A.; Walther, Patrick
ABSTRACT: Understanding the relative influence of environmental and intrinsic effects on populations is important for managing and conserving harvested species, especially those species inhabiting changing environments. Additionally, climate change can increase the uncertainty associated with management of species in these changing environments, making understanding factors affecting their populations even more important. Coastal ecosystems are particularly threatened by climate change; the combined effects of increasing severe weather events, sea level rise, and drought will likely have non‐linear effects on coastal marsh wildlife species and their associated habitats. A species of conservation concern that persists in these coastal areas is the mottled duck ( Anas fulvigula ). Mottled ducks in the western Gulf Coast are approximately 50% below target abundance numbers established by the Gulf Coast Joint Venture for Texas and Louisiana, USA. Although evidence for declines in mottled duck abundance is apparent, specific causes of the decrease remain unknown. Our goals were to determine where the largest declines in mottled duck population were occurring along the system of Texas Gulf Coast National Wildlife Refuges and quantify the relative contribution of environmental and intrinsic effects on changes to relative population density. We modeled aerial survey data of mottled duck density along the Texas Gulf Coast from 1986–2015 to quantify effects of extreme weather events on an index to mottled duck density using the United States Climate Extremes Index and Palmer Drought Severity Index. Our results indicate that decreases in abundance are best described by an increase in days with extreme 1‐day precipitation from June to November (hurricane season) and an increase in drought severity. Better understanding those portions of the life cycle affected by environmental conditions, and how to manage mottled duck habitat in conjunction with these events will likely be key to persistence of the species under future environmental conditions. © 2017 The Wildlife Society. Abstract : Our results indicate that decreases in mottled duck abundance are best described by an increase in days with extreme 1‐day precipitation from June to November (hurricane season) and an increase in drought severity. Intrinsic population drivers such as density dependence contribute less to the variability in mottled duck abundance relative to environmental effects and demographic stochasticity.